2010
DOI: 10.1177/0748233709360200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of acute paraphenylenediamine intoxication in Egypt

Abstract: Orientation to paraphenylenediamine (PPD) acute systemic intoxication in Egypt has been increased over the last decade. The aim of this study was to provide more insight into the clinical profile of acute PPD intoxication with reviewing the possible underlying mechanisms. Our study was retrospective. It was conducted over 7 years (2001-2008) on 25 cases with acute PPD intoxication admitted to the Poison Control Center Ain Shams University Hospitals, Cairo, Egypt. The mean age of the cases was 35.34 +/- 10.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…9,10 In a retrospective study over a period of 7 years (2001-2008) conducted in Egypt, 25 cases of PPD poisoning were identified. 11,12 In the present study which is a two-year prospective study, 79 cases of PPD poisoning were analysed. In this study, maximum incidence was observed in 2 nd and 3 rd decades which are correlating with the study of PK Jain et al In this study, there was female preponderance 76% which is correlating with the studies done by Ayoub Filali et al 8 M.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a retrospective study over a period of 7 years (2001-2008) conducted in Egypt, 25 cases of PPD poisoning were identified. 11,12 In the present study which is a two-year prospective study, 79 cases of PPD poisoning were analysed. In this study, maximum incidence was observed in 2 nd and 3 rd decades which are correlating with the study of PK Jain et al In this study, there was female preponderance 76% which is correlating with the studies done by Ayoub Filali et al 8 M.…”
Section: Discussionmentioning
confidence: 99%
“…PPD is also used in the photographic or rubber industries. In addition, in many African countries, PPD in its pure form or in combination with other natural coloring extracts like Henna, is used for coloring of palms and soles for cosmetic reasons [42] [43]. Unfortunately, there are also vast numbers of unintended and intended incidents of severe to life threatening intoxication involving this synthetic compound [43] [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in many African countries, PPD in its pure form or in combination with other natural coloring extracts like Henna, is used for coloring of palms and soles for cosmetic reasons [42] [43]. Unfortunately, there are also vast numbers of unintended and intended incidents of severe to life threatening intoxication involving this synthetic compound [43] [44]. PPD intoxication leads to a severe clinical syndrome including laryngeal edema, rhabdomyolysis and subsequent renal failure, neurotoxicity and acute toxic hepatitis which per se can lead to dark colored urine [44].…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2 occurs after days or weeks and symptoms include dark cola colored urine, oliguria or anuria due to renal failure, myalgia rhabdomyolysis, Intravascular hemolysis. [3] The management of patient requires multidisciplinary approach and the most important immediate necessity is securing the airway. [4] Tracheostomy is commonly used in most of the institutions to secure the airway.…”
Section: Introductionmentioning
confidence: 99%